Beyond Versus : The Struggle to Understand the Interaction of Nature and Nurture - Tabery, James, 1978- (Book collections on Project MUSE., 2014)
Why the "nature versus nurture" debate persists despite widespread recognition that human traits arise from the interaction of nature and nurture.